Penerapan Nilai-Nilai Profetik pada Pembelajaran Pendidikan Agama Islam dan Budi Pekerti di SMA Negeri 1 Ajibarang - Mahmudatunnisa, Salma; Roqib, Moh. (Jurnal Pendidikan Agama Islam, 2025)
Today, the world of education in Indonesia is facing various challenges at the national, regional and global levels. Then we observe that unconsciously education tends to emphasize the cognitive dimension, and does'nt prioritize the affective dimension and the psychomotor dimension in the education system making an identity crisis so that the loss of noble values inherent in the Indonesian nation such as honesty, politeness, politeness, respect for others, religion and togetherness. Therefore, students need not only knowledge intelligence but also emotional and spiritual intelligence. The purpose of applying prophetic values in learning is to prepare students to be able to implement religious values as exemplified by the Prophet Muhammad. The purpose of this research is to find out and describe the application of prophetic values in Islamic Religious Education and Cultivation learning. This type of research uses descriptive qualitative methods. The research location is SMA Negeri 1 Ajibarang. The subjects of this research include Islamic Religious Education subject teachers and students of class XI-2. This research data collection technique uses observation, interview, and documentation methods. Data analysis techniques use data reduction, data presentation, and data validity techniques using triangulation techniques. The results showed that the Application of Prophetic Values in Islamic Religious Education and Budi Pekerti Learning at SMA Negeri 1 Ajibarang has been well implemented and successful according to its rules. This research recommends the application of prophetic values as a solution for strengthening character values, especially in Islamic Religious Education subjects.